IITA - "Adding value to cassava" - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Peter Kulakow, Cassava, Breeder, IITA - speaks on the work of IITA in adding value to cassava across Africa region. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/